Topographic and hydro-oceanographic feasibility of a chemical port in Morowali - Lastarida Sinaga; Tiara Nofiana; Cahyadi Cahyadi; Wulandari Wulandari; Ira Damayanti; Ganjar Sidik Gandara; Siti Hanan (Universitas Mercu Buana, 2026)
The industrial growth in Morowali Regency, Central Sulawesi, drives the need for port infrastructure to support the distribution of chemicals and fuel. This study aims to evaluate the technical feasibility of developing a liquid bulk terminal in Labota Village, Bahodopi District. The assessment involved hydro-oceanographic and topographic surveys, including a 15-day tidal observation, a 25-hour current measurement, and bathymetric and land surveys. The tidal analysis identified a mixed tide with semi-diurnal dominance and a tidal range of up to 2.66 meters. Current measurements recorded maximum surface speeds of 42 cm/s. Bathymetric data revealed varying depths up to -40 meters and an underwater mound at -10.21 meters, which may require dredging or navigational marking. The land topography is relatively flat and uniform, suitable for port development. Based on these findings, the site is considered feasible for the construction of a liquid bulk terminal capable of serving vessels up to 50,000 DWT with safe maneuvering and berthing operations. This research provides technical recommendations to support industrial logistics in the region, ensuring safe and efficient port operation while considering environmental sustainability. The study offers a comprehensive analysis of chemical and fuel terminal planning in Eastern Indonesia, contributing new insights to port infrastructure development research.